2016
DOI: 10.1155/2016/8329296
|View full text |Cite
|
Sign up to set email alerts
|

A Current Review of the Meniscus Imaging: Proposition of a Useful Tool for Its Radiologic Analysis

Abstract: The main objective of this review was to present a synthesis of the current literature in order to provide a useful tool to clinician in radiologic analysis of the meniscus. All anatomical descriptions were clearly illustrated by MRI, arthroscopy, and/or drawings. The value of standard radiography is extremely limited for the assessment of meniscal injuries but may be indicated to obtain a differential diagnosis such as osteoarthritis. Ultrasound is rarely used as a diagnostic tool for meniscal pathologies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 87 publications
1
60
0
2
Order By: Relevance
“…However, MRI is the most accurate and least invasive for diagnosis of cartilage and meniscal damage [15]. Therefore, a detailed sequence analysis is needed to assemble an optimal sequence protocol to detect chondrocalcinosis and understand its role in joint degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…However, MRI is the most accurate and least invasive for diagnosis of cartilage and meniscal damage [15]. Therefore, a detailed sequence analysis is needed to assemble an optimal sequence protocol to detect chondrocalcinosis and understand its role in joint degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The use of three views can give the full information of the region being analyzed, and therefore, a more detail information of the area. Similar studies support that use images for analysis had showed that the three views are favorable to reconstruct the full image of the region being observed [63] . The three views provide a three-dimensional information of all the sides of the areas being study; therefore, their combination is desired to increase accuracy.…”
Section: Mri Texture and Frequency Attributes 81supporting
confidence: 68%
“…Therefore, the tear was classified as a stage 2B meniscal tear using the Stoller and Crues 3-stage MRI classification of meniscal degeneration. The presence of such a tear accompanied by a huge intrameniscal cyst is very unusual [5][6][7]. Arthroscopy was performed to identify and treat the lesions identified on MRI as an intrameniscal cystic lesion and suspected meniscal tear.…”
Section: Case Presentationmentioning
confidence: 99%